Respostas
respondido por:
6
Aplique a definição
y = log_{a}(b) ⇔ a^{y} = b
![y=\ell og_{\frac{1}{5}}(125)~\Leftrightarrow~(\frac{1}{5})^y=125\\\\(5^{-1})^y=5^3\\\\5^{-y}=5^3 y=\ell og_{\frac{1}{5}}(125)~\Leftrightarrow~(\frac{1}{5})^y=125\\\\(5^{-1})^y=5^3\\\\5^{-y}=5^3](https://tex.z-dn.net/?f=y%3D%5Cell+og_%7B%5Cfrac%7B1%7D%7B5%7D%7D%28125%29%7E%5CLeftrightarrow%7E%28%5Cfrac%7B1%7D%7B5%7D%29%5Ey%3D125%5C%5C%5C%5C%285%5E%7B-1%7D%29%5Ey%3D5%5E3%5C%5C%5C%5C5%5E%7B-y%7D%3D5%5E3)
Agora temos uma igualdade entre potências de mesma base, então:
Ex: a^{b} = a^{c} ⇔ b = c
![-y=3\\\\(-1)y=3\\\\\fbox{$y=-3$}~~\leftarrow~\text{resposta} -y=3\\\\(-1)y=3\\\\\fbox{$y=-3$}~~\leftarrow~\text{resposta}](https://tex.z-dn.net/?f=-y%3D3%5C%5C%5C%5C%28-1%29y%3D3%5C%5C%5C%5C%5Cfbox%7B%24y%3D-3%24%7D%7E%7E%5Cleftarrow%7E%5Ctext%7Bresposta%7D)
y = log_{a}(b) ⇔ a^{y} = b
Agora temos uma igualdade entre potências de mesma base, então:
Ex: a^{b} = a^{c} ⇔ b = c
Perguntas similares
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás